A Survey on Services Provision and Distribution of Official and Commercial Intellectual Property Platforms. (1st August 2020) - Wang, Yang; Gui, Haijin; Ma, Lei
Abstract : Next generation of Information Technologies (IT), such as edging/cloud computing, cybersecurity, and artificial intelligence, has been in a rapid development and therefore concerned wide areas. Management of Intellectual Property Rights (IPR) plays an increasingly important role on knowledge design and engineering, innovation and patent management, intangible assets audition, R&D, and so forth; however, it also meets the challenges from proper platform and service provision, especially when large-scale mobile and distributed requirements become popular. In this paper, Intellectual Property Platforms and corresponding commercial tools have been collected, investigated, and reviewed, involving official platforms in China, USA, EU, and another 6 countries, as well as 12 intellectual property analysis tools commonly used online. Detailed comparison and discussion have been undertaken in order to find potential challenges and opportunities for improved service provision, for example, searching privacy preservation, cloud/edge-based service offloading and efficient distribution, and ontology-based intelligent IPR engineering, which can possibly be commercialised in the near future.